Commercially available antiseptics show high in vitro efficacy against pathogens most commonly associated with canine and feline infectious keratitis - Wolff, Hinrich Tönjes; Piroth, Ana Cristina; Oltmanns, Hilke; Meißner, Jessica; Verspohl, Jutta; Volk, Holger Andreas; Busse, Claudia (Frontiers in Veterinary Science, 2025)
PurposeTo determine the minimal bactericidal concentration (MBC) of polyhexanide (PHMB), povidone-iodine (PVP-I), N-acetylcysteine (NAC), and hypochlorous acid (HOCl) for bacterial species commonly found in canine and feline infectious keratitis.MethodsMBCs for clinical isolates of Staphylococcus (S.) pseudintermedius (n = 11), including 3 methicillin-resistant strains, Pseudomonas (P.) aeruginosa (n = 8), and Streptococcus (Str.) canis (n = 11), including the corresponding control strains, were examined. All testing substances were serially diluted in phosphate-buffered saline (PBS) and cation-adjusted Mueller–Hinton Broth (CAMHB) and inoculated with the bacterial suspension for 10 min. Afterwards, a neutralisation with Dey–Engley neutralising broth was performed, followed by plating onto Columbia sheep–blood agar. After incubation, plates were visually examined for bacterial growth. Tests were carried out in triplicate.ResultsMBCs in PBS for polyhexanide ranged 0.8–1.6 mg/L for S. pseudintermedius and 1.6–3.2 mg/L for P. aeruginosa and Str. canis. For povidone-iodine, MBCs in PBS were observed at concentrations ranging 8–32 mg/L for S. pseudintermedius and P. aeruginosa and 8–16 mg/L for Str. canis. MBCs in PBS for NAC were recorded at a range of 6,400–12,800 mg/L for S. pseudintermedius, whereas those for P. aeruginosa and Str. canis ranged 3,200–6,400 mg/L. Results for HOCl in PBS ranged 0.4–1.6 mg/L for S. pseudintermedius and 0.4–0.8 mg/L for P. aeruginosa and Str. canis. MBCs in CAMHB for polyhexanide were found in the range between 3.2 and >12.8 mg/L, those for povidone-iodine between 6,400 and >12,800 mg/L, and for NAC between 6,400 and >12,800 mg/L, across the tested species. When dissolved in CAMHB, no antimicrobial effect could be observed for HOCl in concentrations up to 137.5 mg/L.ConclusionAll tested substances had an in vitro bactericidal effect against all three bacterial species with MBCs below known tolerated ocular concentrations when dissolved in PBS. Povidone-iodine and hypochlorous acid showed a marked reduction in their in vitro efficacy in the presence of protein. Nevertheless, our results provide a promising outlook on alternatives or adjuvants to antibiotics in ophthalmology that align with the One Health approach.